2018
DOI: 10.3389/fenvs.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Regional Characteristics of Aerosol Pollution in East and Southeast Asia

Abstract: The atmospheric aerosol distribution in Asia is complex because it is influenced by both natural phenomena and human activities. In this article, multifaceted approach using satellite observations and numerical model simulation shows seasonal and regional variations of the aerosol distribution over Asia. Asia covers a large area; however, this article is limited to East and Southeast Asia. The aerosol optical thickness (AOT) in the inland desert area is normally high in spring and dusty aerosols are widely spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A detailed description of this procedure was presented in previous studies. 6,21 The dots in Fig. 13 denote the ADEOS-2/GLI data over the target on August 20, 2003.…”
Section: Retrieval Of Aerosol Properties In Heavy Bba Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of this procedure was presented in previous studies. 6,21 The dots in Fig. 13 denote the ADEOS-2/GLI data over the target on August 20, 2003.…”
Section: Retrieval Of Aerosol Properties In Heavy Bba Eventsmentioning
confidence: 99%
“…Moreover, in urban areas, increasing amounts of small anthropogenic particle emissions are causing an increase in the concentrations of harmful air pollutants, specifically, the well-known suspended particulate matter (PM 2.5 ) in the atmosphere. 5,6 Thus, efficient aerosol retrieval algorithms are required, especially for satellite data on a global scale.…”
mentioning
confidence: 99%
“…Streets et al (2003) reported that BB in tropical forest fires accounted for 73% of the total burning activities every year in Southeast Asia. Recent studies showed that forest burning is the main source of air pollution in this region (Lee et al, 2017;Nakata et al, 2018). However, little is known about the influence of different vegetation types on the HULIS emitted from biomass fires in Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…First, the 20 March, for which the results of field observations are shown in Figure 4, was considered. Satellite observations and numerical model simulations show that aerosol concentrations are high from spring to summer over East Asia (Nakata et al, 2018). Spring is the season when aerosols from mainland China are especially likely to be transported to Japan (Nakata et al, 2015).…”
Section: Mechanisms Of the Mountain Effect On Aerosolsmentioning
confidence: 99%